THE TEACHING OF READING COMPREHENSION BASED ON 2013 CURRICULUM AT SENIOR HIGH SCHOOL - Nainggolan, Elsa Ernawati (Getsempena English Education Journal, 2018)
AbstractThis study aimed at describing how the English teachers of SMA N 1 Raya applied 2013 curriculum in the teaching of reading comprehension. The study employed descriptive qualitative research. The data were collected through observation, in-depth interview, and documentation. The results showed that there were five ways used by the teachers in teaching reading comprehension. They were; asking for studentsâ knowledge, correcting studentsâ pronunciation, asking for the studentsâ comprehension of text, highlighting the moral value of the text, and asking the students to translate the text. However, in reference to 2013 curriculum and the concept of teaching reading, the teaching ways presented by the teachers seemed to be misperceived. The misperception was due to the teachersâ lack of knowledge and skill to realize the concept of curriculum and teaching reading into practice. To achieve one of the final purposes of 2013 curriculum in making students independent reader, the teachers are supposed to master the conceptual knowledge of curriculum and teaching reading to produce the better quality of teaching and learning process. Hence, the teachers would have skills to realize the concept into real teaching behavior to run effective teaching and learning reading in classroom.Â Keywords: 2013 Curriculum, Teaching Reading Comprehension, Senior High School